PISCIS: Platform for Interactive Search and Citizen Science (SciComm Report, 2023)
Many topics in modern astronomy are characterised by the identification of features in images. While this is an easy task for a trained eye, it is difficult to obtain the same quality when performed by models or numerical methods. This has led to cooperation between research teams and citizenship has a long history in different scientific disciplines, due to the great interest of the public, the presence of amateur associations and the constant need for processing large volumes of data. In this work the objective is to present the experience and development of a citizen science web platform (PISCIS, Platform for Interactive Search and CItizen Science), a platform that aims to generate value-added catalogues from data comprising a set of images making use of the citizen’s interest in Astronomy, facilitating the collection and analysis of data as well as making the public aware of the methodology and research topics in the area of Astronomy. A user-friendly application was created for the pollster and the public to create concise surveys and accompany them with images, along with spaces to add information and examples of the surveys to be carried out. The platform is now available. In addition, it is being used to classify the first set of data, consisting of pairs of galaxies, the objective is to catalogue them according to the type of interaction and, for this, examples of pairs with high, medium or low interaction are provided. The collaboration of the public has been important, both in evaluating the platform and in visually inspecting hundreds of galaxy pairs. PISCIS allows people to be linked to research projects, making it possible for a researcher to collect a large amount of data. In order to be able to perform the classifications, training is necessary, so in turn, the participant also learns about science and how it works.
Keywords: classification; web; astronomy; citizen science